(untitled) (International Journal of Scientific Pediatrics, 2025)
Objective. To identify clinical and laboratory features of enteroviral meningitis without pleocytosis in children depending on the presence of cerebrospinal fluid pleocytosis in the Samarkand region. Materials and methods. A retrospective study was conducted of patients under the age of 18 who sought treatment at the Samarkand Infectious Diseases Hospital from May 2016 to May 2023. The patients were divided into 2 groups: 1-group consisted of 7 patients with enteroviral meningitis with pleocytosis in the cerebrospinal fluid, and 2-group consisted of 10 patients without pleocytosis. A quantitative real-time thermal block Exicycler 96 was used for reverse transcription polymerase chain reaction (RT-PCR). Results. All children in both groups complained of headaches. Hyperthermia was complained of by 6 (85.7%) children in 1 group and 8 (80%) children in 2 group. Vomiting was observed in 3 children (42.9%) in 1group and in 4 children (40.0%) in 2 group. Signs of meningeal irritation were positive in all patients in the pleocytosis group and in 8 (80%) patients in the non-pleocytosis group. All patients in the pleocytosis group were hospitalized, and nine (90%) patients in the non-pleocytosis group were refused hospitalization. The peripheral leukocyte counts as well as the mean C-reactive protein level were significantly higher in the pleocytosis group than in the non-pleocytosis group. The median cerebrospinal fluid pressure was higher in the non-pleocytosis group than in the pleocytosis group. Conclusion. Children with meningitis symptoms during an enterovirus epidemic and high cerebrospinal fluid pressure and protein levels should undergo RT-PCR to verify the diagnosis, even if the cerebrospinal fluid leukocyte count is normal.